Propositions and Future Directions of Marketers’ Relationship Effectiveness in Mergers and Acquisitions Integration (Malaysian Management Journal, 2012)
Research on marketing integration related to mergers and acquisitions (M&A) has paid little attention to the combination of similar resources between two similar departments, particularly in the M&A context. Furthermore, existing research does not clearly demonstrate the role of relationship among marketers within the amalgamation process between acquirer and target firm. Hence, this paper addresses a few propositions that relate to strengthening the relationship effectiveness among the marketers in both firms, which at the same time uphold the M&A performance. Collaboration and interaction are proposed as drivers to increase optimistic relationship among the marketers. A quantitative research design is suggested as this method is not popular compared to qualitative methods such as case study, event-study and longitudinal approach in M&A. Drawing from the extant literature, propositions are developed and future directions are presented elaborating success factors to improve M&A integration performance.